2023
DOI: 10.1039/d3nr01987j
|View full text |Cite
|
Sign up to set email alerts
|

Vertical van der Waals heterojunction diodes comprising 2D semiconductors on 3D β-Ga2O3

Abstract: Wide bandgap semiconductors such as gallium oxide (Ga2O3) have attracted much attention for their use in next-generation high-power electronics. Although single-crystal Ga2O3 substrates can be routinely grown from melt along...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 64 publications
(98 reference statements)
1
4
0
Order By: Relevance
“…Our research findings align consistently with those of Wei et al, who demonstrated the outstanding broadband absorption capability of the WS 2 /Ga 2 O 3 heterostructure . In 2023, Leblanc et al built several types of TMDs/Ga 2 O 3 heterostructure devices and ultimately achieved a rectification ratio up to 10 6 in the WS 2 /Ga 2 O 3 heterostructure, showing the great potential of TMDs/Ga 2 O 3 heterostructures to be applied in electronic and optoelectronic devices . Furthermore, it was proven that for broadband photodetection, radiation recombination in TMDs stimulated directly by Ga 2 O 3 by providing electrons through the built-in electric field can not only decrease the series resistance ( R ) but also decrease the junction capacitance ( C ) of the photodetectors by reducing the depletion width.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…Our research findings align consistently with those of Wei et al, who demonstrated the outstanding broadband absorption capability of the WS 2 /Ga 2 O 3 heterostructure . In 2023, Leblanc et al built several types of TMDs/Ga 2 O 3 heterostructure devices and ultimately achieved a rectification ratio up to 10 6 in the WS 2 /Ga 2 O 3 heterostructure, showing the great potential of TMDs/Ga 2 O 3 heterostructures to be applied in electronic and optoelectronic devices . Furthermore, it was proven that for broadband photodetection, radiation recombination in TMDs stimulated directly by Ga 2 O 3 by providing electrons through the built-in electric field can not only decrease the series resistance ( R ) but also decrease the junction capacitance ( C ) of the photodetectors by reducing the depletion width.…”
Section: Resultssupporting
confidence: 89%
“…23 In 2023, Leblanc et al built several types of TMDs/Ga 2 O 3 heterostructure devices and ultimately achieved a rectification ratio up to 10 6 in the WS 2 /Ga 2 O 3 heterostructure, showing the great potential of TMDs/Ga 2 O 3 heterostructures to be applied in electronic and optoelectronic devices. 25 Furthermore, it was heterostructures was apparently improved in the whole wavelength range, especially within the visible range. The Raman spectra showed that the electron density in the TMD layers was all decreased after being transferred onto Ga 2 O 3 films, which was supported by the XPS results.…”
Section: Interlayer Couplingmentioning
confidence: 99%
See 2 more Smart Citations
“…Saturated output currents were observed with a V th of −5.1 V, and a three-terminal breakdown voltage of 144 V was obtained. Leblanc et al [135] demonstrated p-n heterojunctions using p-WSe 2 , WS 2 , and BP on β-Ga 2 O 3 , and the fabricated device structure is depicted in Figure 15g. Their study focused on optimizing 2D/3D vertical diodes on β-Ga 2 O 3 by considering three key factors, including the β-Ga 2 O 3 crystal orientation, the choice of 2D material, and the type of metal contact.…”
Section: β-Ga 2 O 3 Heterostructures With 2d Materialsmentioning
confidence: 99%